Прецизійний генератор хаосу в інваріантних системах зв’язку - Іволга, Л. Г.; Політанський, Р. Л.; Політанський, Л. Ф. (Проблеми телекомунікацій, 2011)
The paper analyzes the development and use of precision chaos generators in communications systems. We have done modeling in Multisim and experimental study of precision chaos generator with improved properties.
Keywords: прецизійний; хаос; синхронізація; генератор